Mulheres e meninas do morro da cruz : reconhecimento do direito à educação como possibilidade de exercício da cidadania - Gomes, Elvira (2018)
The study about the education and citizenship rights continues to be a need and a challenge, especially when is considered women in countryside areas such as the community of Morro da Cruz. Despite significant advances in historical struggles, especially with regard to women's formal education, the results of these struggles did not reach the margins effectively. Thus, the present study sought to understand if it would be the implementation of the right to education a possibility for the exercise of citizenship for girls and women of the community of Morro da Cruz. To obtain data that could answer the question asked, a methodological approach was used to describe the life history with a cut in the school and in the experiences that involve the school life. The study was based on Honneth's theory of recognition and on how he understands the construction of the individual in the three spheres of recognition: love, social esteem or solidarity, and law. Honneth's theory of recognition was used in dialogue with other authors who thought the reality of education in Brazil, rights of citizenship, gender inequalities, feminist struggle, criticism of generalized feminism, inequalities (subalternities) and the opposition of the other. The way the individual's identity is being built and recognized or not in the three spheres of Honneth's recognition, in a way, will result in his life and especially in his education. For this reason, this text sought to bring both the issue of work and housing and other rights of citizenship to show how their lack influenced and influenced the access of girls and women to formal education and, as a consequence, the impossibility of exercising citizenship. It was also possible to perceive some gaps in the public policies that a minority finds and that can serve as a trail for new horizons.